2009
DOI: 10.1586/eog.09.12
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding of endometrial stem cells

Abstract: Somatic stem cells (SSCs) are defined as a rare population of undifferentiated cells residing in differentiated tissues and organs. Different studies and diverse approaches suggest the presence of SSCs in human and murine endometria. Owing to the lack of specific phenotypic markers to identify endometrial SSCs, they are defined by their functional properties. The embryological origin of the uterus and the putative implication of bone marrow in endometrial regeneration suggest their presumed mesenchymal origin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…Human endometrium regenerates on a cyclic basis from proposed progenitors of epithelial, fibroblast, and endothelial origins [6][7][8]. We found that eMSCs express markers of pericytes (e.g., RGS5, ACTA2, ANGPT2, IGFs, NGF and NGF high-affinity receptors, PDGF, PTHLH, TGFB, and syndecan) [48][49][50][51], and our immunofluorescence studies confirm the perivascular localization of these cells [21].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Human endometrium regenerates on a cyclic basis from proposed progenitors of epithelial, fibroblast, and endothelial origins [6][7][8]. We found that eMSCs express markers of pericytes (e.g., RGS5, ACTA2, ANGPT2, IGFs, NGF and NGF high-affinity receptors, PDGF, PTHLH, TGFB, and syndecan) [48][49][50][51], and our immunofluorescence studies confirm the perivascular localization of these cells [21].…”
Section: Discussionsupporting
confidence: 78%
“…At menses and postpartum the endometrium exhibits a proinflammatory environment, extensive extracellular matrix remodeling, vasospasm, hypoxia, cell death, and tissue desquamation, with wound repair mechanisms and cellular proliferation and differentiation participating in its regeneration without scarring [2][3][4][5]. Stem/progenitor cells (epithelial, mesenchymal, endothelial) likely contribute to the rapid endometrial cyclic growth and regeneration of 4-14 mm of mucosa per cycle during the more than 400 cycles in a woman's reproductive lifespan and endometrial regeneration/ repair postpartum [6][7][8]. It is well known that bone marrowderived mesenchymal stem cells (MSCs) in the circulation can home to sites of damaged tissues [9], and it has been postulated that bone marrow-derived MSCs participate in cyclic endometrial repair and regeneration and may be progenitors of stromal fibroblasts and perhaps epithelial cells in the endometrium [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the content of MSC does not exceed a few parts of a percent, working with them implies isolation and cultivation in vitro. The most accessible sources of mesenchymal stem cells are fatty tissue, umbilical cord blood and placenta [16][17][18].…”
Section: Commentarymentioning
confidence: 99%